Kandungan logam berat besi (Fe) pada air dan daging ikan lemeduk (Barbonymus schwanenfeldii) di Sungai Belumai Deli Serdang - Surbakti, Nur Anisah Br; Febriani, Husnarika; Syukriah, Syukriah (Universitas Batangahari Jambi, 2024)
The Belumai River is used for various societal activities as well as a disposal site for residual waste from domestic and industrial activities. One of the fishes in the Belumai River is tinfoil barb (Barbonymus schwanenfeldii). The purpose of this study is to analyze the content of iron (Fe) metals in river water and fish meat. Sampling points or stations for river water and tinfoil barb (Barbonymus schwanenfeldii) used a purposive sampling method. The content of Fe at stations I, II, and III in water also meat of tinfoil barb (Barbonymus schwanenfeldii) was 1,99 mg/L, 2,65 mg/L and 1,99 mg/L while in fish meat it was 27,02 mg/kg, 43,57 mg/kg and 88,42 mg/kg. The results of testing for Fe metal in river water and tinfoil barbâ€™s meat (Barbonymus schwanenfeldii) have passed the water quality standard limits according to PP RI No. 22 of 2021 (0.03 mg/L) and JECFA 2020 (0.8 mg/kg). The BCF grade at station I is 13,57 L/kg, station II is 16,44 L/kg, and III is 44,37 L/kg.Â